Breast cancer in the elderly. Issue 841 (November 1995) - Bellet, M.; Alonso, C.; Ojeda, B.
Abstract : Breast cancer in the elderly has attracted considerable interest in recent years for three main reasons. Firstly, information concerning the profile (clinical and biological) of the disease in the geriatric population is scarce; secondly, the number of patients is increasing, and thirdly there are conflicting data regarding the actual effectiveness of the different treatments. The present review attempts to outline the specific characteristics of this malignancy in the elderly in terms of histological pattern, stage at diagnosis, and outcome. The feasibility of standard therapies (mastectomy/lumpectomy, axillary clearance, and radio-therapy) in the elderly is carefully analysed, and compared to the efficacy of less aggressive procedures. The use of tamoxifen as a primary treatment, instead of surgery, is critically reconsidered, as well as its use as an adjuvant therapy. Finally, the effectiveness of systemic therapy in advanced disease is also discussed.